PHYSICS COMPREHENSIVE CONTEXTUAL TEACHING MATERIAL UNTUK MENINGKATKAN KEMAMPUAN ARGUMENTASI - Muhammad Zaini; Nugroho Prasetya Adi; Lalu Usman Ali (Universitas Islam Negeri (UIN) Mataram, 2020)
Contextual Teaching Learning (CTL) is learning based on contextual events in daily life. The development of teaching materials assisted by android applications in learning physics is a very necessary thing and needs to be carried out continuously. This research aims to produce android-assisted PhyCCTM teaching materials that can improve the ability of argumentation. This research is research and development. The development procedure refers to the development model adapted from the 4D model which consists of four stages namely defining, designing, developing, and distributing. Content validation was carried out by four lecturers and seven physics teachers. Field trials are carried out in schools by applying the quasi-experimental method and using the control group pretest and posttest design. The trial was conducted by taking two classes as experimental and control classes. Improvement and differences in the results of students' argumentation abilities in the experimental and control groups were done by t-test. The research results obtained are android-assisted PhyCCTM teaching materials to improve the ability of argumentation worthy to be used with the category of